Impact of Exchange Rate Fluctuation on Selected Economic Sectors of the Nigerian Economy - Victor C, NDUBUAKU; Kizito, ONWUKA; Chukwuka, ONYEDIKA; Chinonye, CHIMEZIE Isabella (International Journal of Sustainable Development & World Policy, 2019)
The study investigated the impact of exchange rate fluctuation on selected economic sectors of the Nigerian economy. The study covered the agricultural (AGDP), manufacturing (MGDP), petroleum (PGDP) and service sector (SGDP) of the Nigerian economy. The petroleum sector represented the oil sector while the agricultural (AGDP), manufacturing (MGDP), and service sector (SGDP) represented the non-oil sector. The main objective of the study was to determine whether exchange rate fluctuations had a significant impact on the selected sectors of the economy. These sectors were invariably the largest contributors to the GDP. The time scope covered 1981-2016. Data for the study were obtained specifically from CBN statistical bulletin (2016). The data were analysed using the Auto Regressive Distributed Lagged (ARDL) model. The study concluded that there was no significant impact of exchange rate on AGDP, MGDP and SGDP respectively. However, there was a positive and significant impact of exchange rate on PGDP. The study recommended that Nigeria’s economy should be diversified to enable the non-oil sector to become significant foreign exchange earners.